1994
DOI: 10.1016/0014-5793(94)00380-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid‐binding regions of the second‐largest subunit of Drosophila RNA polymerase II identified by Southwestern blotting

Abstract: Analysing overlapping bacterially expressed fragments of the second-largest subunit of Drosophila melanogaster RNA polymerase II in Southwestern DNA binding assays we have identified regions that have the potential to bind nucleic acids non-specifically.A region exhibiting strong DNA binding is located in the N-terminal part of the molecule (amino acids 357-504) and some weak DNA binding is observed for the C-terminal part (amino acids 860-l 160). The non-specific DNA binding behavior of these regions is simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“….. Weilbaecher et al, 1994), in yeast class II (rpbl-14, Scafe et al, 1990;sua8, Berroteran et al, 1994) or class III (rpcl6O-112, Dieci et al, 1995) RNA polymerases were represented on this diagram by calculating their corresponding position in the Algo gene from the center of conserved region d. Hatched regions in (B) and (D) were described to bind nucleic acid (Allison et al, 1985;Kontermann et al, 1993;Kontermann and Bautz, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“….. Weilbaecher et al, 1994), in yeast class II (rpbl-14, Scafe et al, 1990;sua8, Berroteran et al, 1994) or class III (rpcl6O-112, Dieci et al, 1995) RNA polymerases were represented on this diagram by calculating their corresponding position in the Algo gene from the center of conserved region d. Hatched regions in (B) and (D) were described to bind nucleic acid (Allison et al, 1985;Kontermann et al, 1993;Kontermann and Bautz, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…If this interpretation were correct, the DNA would be expected to slide at the base of the stalk. Accordingly, the epitope recognized by the anti-AI35 antibody was mapped 22 residues away from conserved domain C which was shown to bind DNA ( Figure 8B, Allison et al, 1985;Kontermann and Bautz, 1994). Alternatively, the antibody may interfere with a conformational change of the enzyme involving the fingerlike stalk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on May 11, 2018 by guest http://mcb.asm.org/ largest subunit of yeast RNA polymerase III thought to be associated with RNA product binding (22,25,34) are able to compensate for the SUP4-CTC2 defect, completely restoring in vivo suppression to SUP4 levels (50).…”
Section: Discussionmentioning
confidence: 99%
“…DNA blotting, ultraviolet cross-linking, and antibody inhibition studies indicated the involvement of subunit 1, the homologue of the E. coli RNA polymerase ␤Ј subunit, in DNA binding (1)(2)(3)(4)(5), whereas subunit 2, the homologue of the E. coli ␤ subunit, has binding sites for nucleotide substrates (6 -9) and DNA (1,10,11). S. cerevisiae pol II subunit 3 (RPB3) and the corresponding subunits from other organisms have a limited sequence similarity to the E. coli ␣ subunit.…”
mentioning
confidence: 99%